EFFECTIVENESS OF USING DIGITAL MARKETING TOOLS IN THE B2B MARKET (Marketing Journal, 2025)
This article analyzes the main directions of digital marketing, particularly its significance in B2B marketing and the digital technologies being applied in this field. The main goal of the research is to study digital marketing strategies and technologies in the context of B2B marketing and to identify existing opportunities and challenges through SWOT analysis. The literature review shows that scientific research on the use of digital technologies specifically in the B2B sector has not been sufficiently developed. This article aims to fill that gap.
Keywords: Digital marketing; B2B marketing; SWOT analysis; strategic planning; e-commerce; artificial intelligence